2014
DOI: 10.1515/hc-2014-0093
|View full text |Cite
|
Sign up to set email alerts
|

Cyclopropyl aziridines: solvolytic reactions of the N-tosylaziridines of (+)-2-carene and (+)-3-carene

Abstract: The N-tosylaziridine 4 of (+)-2-carene 1 was prepared and subjected to solvolytic reactions with weak protic acids. For comparison, the solvolytic reactions of cis-3-carene-N-tosylaziridine 8 were also studied. The solvolyses of 4 were more rapid than those of 8, and both rings were opened in 4, whereas only the aziridine was opened in 8. This leads to the conclusion that the aziridine and cyclopropane rings in 4 can achieve a conjugated transition state.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 52 publications
0
3
0
Order By: Relevance
“…It has been demonstrated that the reactivity of the cyclopropyl halonium ions of compound 1 is similar to that of the protonated cyclopropyl epoxide 2 [6] and cyclopropyl tosylaziridine 5 [10]. As expected, the cyclopropyl halonium ions were extremely reactive, but acetonitrile was able to trap them, with 1,4-addition occurring, opening the cyclopropane ring, instead of 1,2-addition occurring, as occurs with halonium ions of compound 3 [27].…”
Section: Resultsmentioning
confidence: 69%
See 2 more Smart Citations
“…It has been demonstrated that the reactivity of the cyclopropyl halonium ions of compound 1 is similar to that of the protonated cyclopropyl epoxide 2 [6] and cyclopropyl tosylaziridine 5 [10]. As expected, the cyclopropyl halonium ions were extremely reactive, but acetonitrile was able to trap them, with 1,4-addition occurring, opening the cyclopropane ring, instead of 1,2-addition occurring, as occurs with halonium ions of compound 3 [27].…”
Section: Resultsmentioning
confidence: 69%
“…We have since found similar behaviour with the tosyl aziridines 5 and 6 (Scheme 3) [8][9][10]. We suggested that in the reactions of compound 2 or 5 with water, the positive charge on the protonated heteroatom was delocalized through the cyclopropane [8][9][10][11][12][13] and both rings were opened in a concerted fashion by the oxygen nucleophile (Scheme 2). This released the strain energy of both rings.…”
Section: Introductionmentioning
confidence: 75%
See 1 more Smart Citation